2019
DOI: 10.1267/ahc.19014
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Conversion among Subtypes of Salivary Gland Duct Cells as Identified by Production of a Variety of Bioactive Polypeptides

Abstract: Four major kallikreins (mK1, mK22, mK9, and mK13) were identified in the mouse submandibular gland (SMG). mK1, a true tissue kallikrein, was used as a protein marker to identify different types of SMG granular convoluted tubule (GCT) cells along with epidermal growth factor (EGF), nerve growth factor (NGF), and renin. Kallikrein mK1 was localized in a very small number (~5%) of GCT cells, which were scattered throughout the GCT, indicating that the majority of GCT cells are mK1-negative. Among mK1-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The shift of FGF10 expression from mesenchymal to epithelial cells is intriguing and observed within a very narrow postnatal time frame. The differentiation of duct cells occurs between 1 and 2 weeks after birth ( Kurabuchi et al, 2019 ), which correlates with the timing of the FGF10 expression shift. Differentiation of GCT cells is normally under hormonal control of androgens (dihydrotestosterone) and possibly other hormones ( Kurabuchi et al, 2019 ; Morrell et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift of FGF10 expression from mesenchymal to epithelial cells is intriguing and observed within a very narrow postnatal time frame. The differentiation of duct cells occurs between 1 and 2 weeks after birth ( Kurabuchi et al, 2019 ), which correlates with the timing of the FGF10 expression shift. Differentiation of GCT cells is normally under hormonal control of androgens (dihydrotestosterone) and possibly other hormones ( Kurabuchi et al, 2019 ; Morrell et al, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of duct cells occurs between 1 and 2 weeks after birth ( Kurabuchi et al, 2019 ), which correlates with the timing of the FGF10 expression shift. Differentiation of GCT cells is normally under hormonal control of androgens (dihydrotestosterone) and possibly other hormones ( Kurabuchi et al, 2019 ; Morrell et al, 1987 ). Mice treated with thyroid hormones and androgens convert SD cells into the GCT-like cells ( Kurabuchi, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nerve growth factor (NGF) is produced and stored in the secretory granules by GD cells beginning when mice are 2–3 weeks old. 29 , 30 The staining and quantitative image analysis indicated that NGF contents significantly decreased in the GD cells of Ift140-cKO glands compared with WT (Fig. 5d–f , quantified in m, n), which suggested that granule contents were dysregulated in the absence of IFT140.…”
Section: Resultsmentioning
confidence: 94%